Using quickplace for sending counseling report online - Ho, Leong Wai. (Universiti Malaysia Sarawak (UNIMAS), 2003)
With the advancement of technology, many day to day works is being made easier. Computers and the internet having the most advancement in such a short period of time arc not being fully utilized by the counseling profession in Malaysia. The study attempts to use QuickPlace (a collaborative application) for sending counseling reports online. A sample of 59 counselling students from Universiti Malaysia Sarawak were selected to for the research purpose. Descriptive method was used to analyze the data from the evaluation of the website on its design, content and accessibility. The results show that respondents have very positive feedback towards the usage of QuickPlace for counselling report sending in tenns of ease of use but cautioned on the confidentiality of the reports being sent online.